Smart design, science & technology : proceedings of the IEEE 6th International Conference on Applied System Innovation (ICASI 2020), November 5-8, 2020, Taitung, Taiwan /: proceedings of the IEEE 6th International Conference on Applied System Innovation (ICASI 2020), November 5-8, 2020, Taitung, Taiwan. (2021) - Unknown
No abstract available